Preface-ISPRS workshop on advanced geospatial applications for smart cities and regions (smartgeoapps 2019) - Agugiaro, G. (International Society for Photogrammetry and Remote Sensing, 2021)
10.5194/isprs-archives-XLII-2-W13-1287-2019